A Novel Blood Index-Based Model to Predict Hepatitis B Virus-Associated Hepatocellular Carcinoma Recurrence After Curative Hepatectomy: Guidance on Adjuvant Transcatheter Arterial Chemoembolization Choice - Zou, Yiping; Chen, Zhihong; Lou, Qi; Han, Hongwei; Zhang, Yuanpeng; Chen, Zhenrong; Ma, Zuyi; Shi, Ning; Jin, Haosheng (Frontiers in Oncology, 2021)
Background: Postoperative recurrence is a significant obstacle in hepatocellular carcinoma (HCC) treatment. This study aimed to construct a blood index-based model to predict hepatitis-B virus-associated HCC (HBV-HCC) recurrence after curative hepatectomy. Methods: A total of 370 patients who received initially curative hepatectomy for HBV-HCC were included in this study. A novel blood index signature (BIS) was identified and systematically analysed for its recurrence predictive value. Following this, multivariate Cox regression analysis was performed to build a blood index-based nomogram. Results: A BIS based on aminotransferase to platelet ratio index and systemic-inflammatory response index was used to construct a nomogram. The model showed good clinical applicability and reliability. Notably, the patients in the high-recurrence risk group tended to benefit from adjuvant transcatheter arterial chemoembolisation (TACE). Conclusion: A reliable model was constructed to predict the HBV-HCC recurrence after curative hepatectomy. This model can guide the surgeons in selecting patients with high recurrence risk patients who may benefit from adjuvant TACE.